2010
DOI: 10.1021/jp102710m
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde Polymerization on (WO3)3/TiO2(110) Model Catalyst

Abstract: Polymerization of formaldehyde, H2CO, was studied under ultrahigh vacuum conditions on a model catalyst consisting of monodispersed (WO3)3 clusters anchored on TiO2(110). Formaldehyde oligomers, (H2CO) n , desorbing from the polymer that formed on the catalyst surface are detected between 250 and 325 K in temperature-programmed desorption experiments. At least two monolayers (ML) of H2CO are required on the surface to observe (H2CO) n , desorption and the amount saturates for H2CO coverages in excess of ∼40 ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
131
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(140 citation statements)
references
References 38 publications
9
131
0
Order By: Relevance
“…As we have shown recently, this reaction also proceeds via methoxy intermediates, that are, thus, sufficiently available. 15 We also rule out the possible oligomerization of formaldehyde, that was reported at WO 3 catalysts below 100 K. [29][30][31] We do not expect this to be limiting here because the methane desorption proves that remaining methoxy sites are present which indicates that less formaldehyde was produced than on bare TiO 2 . Moreover, Dohna ´lek et al point out, that at least two monolayers of formaldehyde are required to yield reasonable amounts of oligomers.…”
Section: Impact Of Tungsten Oxide Clusters On Photochemical Reactionsmentioning
confidence: 94%
See 1 more Smart Citation
“…As we have shown recently, this reaction also proceeds via methoxy intermediates, that are, thus, sufficiently available. 15 We also rule out the possible oligomerization of formaldehyde, that was reported at WO 3 catalysts below 100 K. [29][30][31] We do not expect this to be limiting here because the methane desorption proves that remaining methoxy sites are present which indicates that less formaldehyde was produced than on bare TiO 2 . Moreover, Dohna ´lek et al point out, that at least two monolayers of formaldehyde are required to yield reasonable amounts of oligomers.…”
Section: Impact Of Tungsten Oxide Clusters On Photochemical Reactionsmentioning
confidence: 94%
“…Such clusters on various supports were already tested in theoretical and experimental studies for thermal alcohol or aldehyde conversion reactions. [24][25][26][27][28][29][30][31][32] Surprisingly, the photochemistry of these clusters has not been investigated yet although both materials (WO 3 and TiO 2 ) are promising candidates for photochemical reactions. Moreover, the band gap of bulk WO 3 (2.8 eV) is smaller than the one of rutile TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…23À25 Our catalytic studies of (WO 3 ) 3 embedded in an alcohol matrix and/or supported on TiO 2 (110) and Pt(111) demonstrated that the Lewis acid/base chemistry of WdO groups plays a prominent role in alcohol chemistry, leading to formation of alkenes, aldehydes, ketones, and ethers, 13,14 and in the polymerization of formaldehyde. 20,21 To further understand the interactions of (WO 3 ) 3 with oxide supports, we focus on (WO 3 ) 3 cluster deposition on a FeO(111) overlayer grown on Pt(111). 26 In contrast with TiO 2 (110), which has important catalytic properties on its own, we expected the oxygen-terminated FeO(111) surface to be significantly less reactive and therefore ideal as an inert support for our (WO 3 ) 3 clusters.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Among them, increasing interest has been devoted to tungsten oxide, which has been found to accelerate many types of reactions, 4 such as alkane isomerization, 5 alkene metathesis, 6 alcohol oxidation, 7 and selective NO reduction. 8 In recent years, tungsten oxides loaded on different supports such as TiO 2 , 9,10 Cu-O 11 and FeO/Pt(111) 12 by direct sublimation of WO 3 have been extensively studied in an attempt to correlate the structure with catalytic performance, like dehydration of 2-propanol, 13 oxidation and reduction of aliphatic alcohols, 14 or polymerization of formaldehyde 15 and acetaldehyde, 16 which has suggested that the catalytic properties of tungsten oxides are strongly inuenced by the support.…”
Section: Introductionmentioning
confidence: 99%